El art. 190 del código civil ecuatoriano, vulnera el derecho constitucional a la vivienda del otro cónyuge, afectando al buen vivir” “Necesaria Reforma” - Guevara Sanchez, Willians Ernesto (2015)
The adoption of the new Constitution of Ecuador represents a breakthrough for the realization of the right to a dignified city in the region. The text, endorsed the September 28, 2008 to replace the previous 1998 Constitution, innovatively addresses the right to housing and a dignified city. From the Preamble, the scope of the good life - sumak kawsay in Quechua appear as primary objective of the nation and essential for peaceful coexistence in diversity and harmony with nature condition. There are several economic, social and cultural, individual and collective human rights, which are regulated within the framework of "the rights of good living" (Articles 12-34 of Chapter II), such as the right to water, to a healthy environment , habitat and housing, culture and science, etc. The right to housing is embedded in the broader context of the village, the city and the environment in general, that is, that of a safe and healthy habitat as guaranteed by Article 30 of the Constitution. However there is a violation of the constitutional right to housing, the provision of Art. 190 of the Civil Code, which says if there is one social good for housing shall be conferred legal right of use and occupancy for the spouse who be entrusted with the care of minor children, including the holder of the use and occupancy has power to exercise possessory action (under possession) against the spouse who attempts to violate the prohibition to cohabit, this contradiction to the right to 50 % of acquisitions of one spouse undoubtedly affects the other spouse is entitled to fifty percent of acquisitions over good for housing, and therefore the ban is absurd to cohabit in a well in which it is entitled property. The impossibility of cohabitation lasts until the children stop being incapable, which affects greatly if the child is a newborn, which means that for 18 years can not live together in a house that has 50% of the property.